2013
DOI: 10.1159/000348676
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis-Induced Neutrophil Extracellular Traps Activate Human Macrophages

Abstract: Neutrophils activated by Mycobacterium tuberculosis (Mtb) form neutrophil extracellular traps (NETs), containing DNA and several biologically active cytosolic and granular proteins. These NETs may assist in the innate immune defense against different pathogens. We investigated whether the NET-forming neutrophils mediate an activating signal to macrophages during the early multicellular inflammatory reaction and granuloma formation. Mtb-induced NETs were found to be reactive oxygen species dependent and phagocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
159
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 43 publications
8
159
0
2
Order By: Relevance
“…After induction of apoptosis, the apoptotic neutrophils are recognized and cleared by other adjacent phagocytes. While studies in our lab have shown that uptake of neutrophils, which are apoptotic as a consequence of phagocytosing mycobacteria, by human macrophages induces a proinflammatory response in the macrophage (387)(388)(389), uptake of spontaneously apoptotic neutrophils have long been implicated in anti-inflammatory responses and resolution of inflammation (390). However, since the site of infection at early stages likely contains both mycobacteria-infected and spontaneously apoptotic neutrophils, a downregulation of macrophage responses by the latter could have detrimental effects for the host.…”
Section: Paper IVmentioning
confidence: 95%
“…After induction of apoptosis, the apoptotic neutrophils are recognized and cleared by other adjacent phagocytes. While studies in our lab have shown that uptake of neutrophils, which are apoptotic as a consequence of phagocytosing mycobacteria, by human macrophages induces a proinflammatory response in the macrophage (387)(388)(389), uptake of spontaneously apoptotic neutrophils have long been implicated in anti-inflammatory responses and resolution of inflammation (390). However, since the site of infection at early stages likely contains both mycobacteria-infected and spontaneously apoptotic neutrophils, a downregulation of macrophage responses by the latter could have detrimental effects for the host.…”
Section: Paper IVmentioning
confidence: 95%
“…However, they can also recognize damage-associated molecular patterns (DAMPs) during tissue-damage and participate in viral host defense [12,13] . Another important function is the formation of neutrophil extracellular traps (NETs), formed during an active cellular process where the neutrophil releases its DNA to the extracellular environment [14,15] . Finally, resolution of neutrophil inflammation has to be tightly regulated to avoid accumulation of these cells, as is exemplified by the prolonged and excessive inflammation in cystic fibrosis [16][17][18] .…”
mentioning
confidence: 99%
“…Another more recently described way for neutrophils to counteract bacterial dissemination is through the release of nuclear DNA resulting in the formation of NETs [14] . S. pyogenes , like many other bacterial species, can escape entrapment in NETs through the release of extracellular DNase [15,16] .…”
mentioning
confidence: 99%